Perbedaan Efektivitas Massage Rubbing Punggung Menggunakan Power Massager Dan Massage Rubbing Punggung Menggunakan Tangan Terhadap Penurunan Nyeri Pada Pasien Primigravida Inpartu Kala I Fase Aktif - Maria Magdalena Theofila Duka (Pusat Riset dan Inovasi Nasional, 2023)
Childbirth is a series of events when a baby is released from the mother's womb, followed by the release of the placenta and fetal membranes from the mother's body (Fitriana and Nurwiyandani, 2018). Experimental research method with a design that is Control group pre test-Post test. The population in this study were all primigravid postpartum patients without complications during the first active phase in the working area of ​​the Halilulik Health Center, Naitimu Village, West Tasifeto District, East Nusa Tenggara, Using a purposive sampling technique, a sample of 16 people was obtained with a distribution of 8 people for the back rubbing massage treatment using the Power Massager (group 1) and 8 people for the back rubbing massage treatment using the hands (group 2). The results showed that the back rubbing massage treatment using a power massager obtained an average decrease in pain of 2.375, while the treatment of back rubbing massage using hands obtained an average decrease in pain of 1.250, obtained P count of 0.0013 P <0.05, So it can be concluded that back rubbing massage using a power massager is more effective than using hands in reducing pain in primigravida in parturient patients in the active phase 1. In conclusion, back rubbing massage using a power massager is more effective in reducing pain in primigravid patients in labor in the first active phase.